Victims’ participation in the proceedings, reparations to victims, and lessons learnt, unlearnt, and might have been learnt - Pellet, Sarah (The ICC at 25: Lessons Learnt, 2025)
For a long time, victims of the ‘unimaginable atrocities that deeply shock the conscience of humanity’ were considered at best as mere witnesses, testifying for the Prosecutor – and more rarely for the Defence. It was only with the adoption of the Rome Statute in 1998 that victims were placed at the heart of international criminal justice, recognising for the first time the possibility of their participating in proceedings before an international criminal jurisdiction and claiming reparation for the harm they suffered. But what is the reality from the victims’ perspective?Keywords: Victims, participation, reparations, International Criminal Court, Trust Fund for Victims